REAKSI PASAR PADA PENGUMUMAN EMPLOYEE STOCK OPTION PLAN - Agus Kusuma, I Made Gede; Sadha Suardikha, I Made; Dwirandra, A.A.N.B (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.11.TAHUN 2016, 2016)
The sampling method used in this research is purposive sampling and obtained samples of 36 companies and 193 events that apply ESOP of the year January 1, 2002 tvvo March 31, 2016. The data used is secondary data such as the date of the announcement of events ESOP, stock market prices and financial statement. To prove the hypothesis testing One- sample t-test and simple regression.The research proves that the market reacted negatively on events ESOP announcement. The study also proved that the number of stock options granted by affecting the amount of abnormal return. Both the results of this study indicate that the ESOP are considered to have prospects companies that provide benefits in the future and the enormous amount of stock options granted is able to give a positive abnormal return after the announcement of ESOP because the motivation of management to maximize the benefits of the ESOP program given to him.
Keywords: employee stock option plan (ESOP), abnormal return